Clinical Research of Mortality in Emergency Air Medical Transport. (4th August 2014) - Chen, Wan-Lin; Ma, Hon-Ping; Wu, Chih-Hsiung; Chiou, Hung-Yi; Yen, Yun; Chiu, Wen-Ta; Tsai, Shin-Han
Abstract : Introduction. EAMT in Taiwan has experienced increasing demand in the past few years. The objective is to analyze the trend of EAMT in the past six years and mortality rate within three days of patients undergoing interfacility transport in Taiwan. Material and Method. We conducted a retrospective review of patients who were airlifted from remote islands to main island between 2006 and 2011. Main outcome measures are EAMT number (EAMT- N ), EAMT per thousand population (EAMT frequency, EAMT- F ), number of mortality (Mor- N ), and mortality rate within three days after EAMT (Mor- R ). Results and Discussion. Overall mortality rate is 7.54% in 1684 airlifted patients. Acute myocardial infarction (AMI, 26.3%) and traumatic brain injury (TBI, 25.8%) comprise the majority in diagnosis (52.1%). However, Mor- R in these two categories is significantly low in AMI (3.5%) and TBI (5.1%). Conclusion. The present study demonstrates that physician density is not related to EAMT- N but to physician number. As general population ages (10%), the average age of patient who underwent EAMT doubled (21%). This study also leaves room for discussion regarding futile medical care. The results can be used as a reference for increasing utilization of EAMT in current National Health Care Scheme.